Advanced circuits for emerging technologies - Iniewski, Krzysztof, 1960- (John Wiley & Sons, 2012)
Covers advanced circuits for emerging technologies including digital VLSI, analog VLSI, and VLSI memories Complementary metal oxide semiconductor (CMOS) technology is the dominant technology for fabricating integrated circuits. It is reliable, manufacturable, low power, low coat, and most importantly, scalable. Advanced Circuits for Emerging Technologies provides professionals working in the integrated circuit design field with the many start-of-the-art techniques being utilized today. Covering exciting developments in body area networks, wireless communications, data networking, and optical imaging, this authoritative book discusses emerging materials that can take system performance beyond standard CMOS--like Silicon on Insulator (SOI), Silicon Germanium (SiGe), and Indium Phosphide (InP)--and describes three-dimensional (3-D) CMOS integration and co-integration with sensor technology. Divided into four parts, Advanced Circuits for Emerging Technologies covers: Digital design and power management Analog and RF wireless circuits Device layout and reliability topics Ever increasing device testing issues Written by top-notch international experts in industry and academia, Advanced Circuits for Emerging Technologies is a must-read for anyone serious about circuit design for future technologies.